Audio-visual aids as a technique in the education of the educable mentally retarded children - Llanes, Aurora L. 1938- (1967)
This discussion was made to show the effectiveness of visual aids as a technique in teaching the educable mentally retarded children. The study identified audio-visual aids and their implications in the learning process and some of the audio-visual aids used at present in teaching the educable mentally retarded children.
Thesis (M.A.T. Special Education)--University of the Philippines, Diliman.
Keywords: Mentally handicapped children -- Education; Audio-visual education